A practical method to investigate the effect of volatile organic compounds emitted by rhizobacteria on plant growth under conditions of salt stress - Cappellari, Lorena del Rosario (2023)
Salinity is one of the causes that limit crop production. Plant Growth Promoting Rhizobacteria (PGPR) are beneficial soil bacteria that play a significant role in promoting plant growth. These microorganisms can produce their effect through the emission of Volatile Organic Compounds (VOCs). Most of the research to study the effects of microbial VOCs on plant growth has been carried out under controlled conditions using partitioned Petri dishes. In this article, we describe an alternative method that has the advantage of allowing long-term trials, being able to let the plant have a greater development in growth and height, without space limitation. In the proposed method, M. piperita were planted in glass jars containing Murashige and Skoog solid media, with a small glass vial containing Hoagland media inserted into the jar. This small vial was inoculated with the specified bacterium and served as the source of bacterial volatiles. This way plants were exposed to mVOCs without having any physical contact with the rhizobacteria.